Oxygen uptake kinetics during low intensity exercise: relevance for rate adaptive pacemaker programming. Issue 2 (February 1997) - Lewalter, T.; Rickli, H.; MacCarter, D.; Jung, W.; Schimpf, R.; Schwartze, P.; Candinas, R.; Lüderitz, B.
Abstract : OBJECTIVE: To establish a normal database for oxygen uptake (VO2) kinetics during low intensity treadmill exercise (LITE) testing, to be used as a guideline for programming rate adaptive pacemakers, and to determine its relation to VO2 at anaerobic threshold and peak exercise. DESIGN: VO2 kinetics during LITE were compared with VO2 at anaerobic threshold and at peak exercise. SETTING: LITE testing is applicable during ambulatory or hospital care and can even be performed by patients with reduced cardiac capacity. PATIENTS: 60 healthy subjects (23 women, 51.6 (SD 20.4) years; 37 men, 42.2 (16.2) years). INTERVENTIONS: Treadmill exercise testing with "breath by breath" gas exchange monitoring using the LITE protocol for steady state, submaximal exercise, and the ramping incremental treadmill exercise (RITE) protocol for peak exercise. MAIN OUTCOME MEASURES: Mean response time of VO2, mean oxygen deficit, and VO2 at anaerobic threshold (VO2-AT) and at peak exercise (VO2-peak) were determined. RESULTS: (1) LITE protocol: mean response time of VO2 = 35.1 (9.9) s; oxygen deficit = 418.3 (47.9) ml; oxygen deficit/VO2 time index = 54.7 (7.4). (2) RITE protocol: VO2-AT = 22.1 (5.7) ml/kg/min; heart rate at anaerobic threshold = 120.1 (3.6) beats/min; VO2-peak = 37.6 (10.7) ml/kg/min; peak heart rate = 167.8 (19.3) beats/min. The mean response time and oxygen deficit/VO2 time index were significantly correlated to VO2-peak and VO2-AT (P < 0.01). CONCLUSIONS: VO2 kinetics calculated in healthy controls may serve as a control database for assessing the rate response programming of pacemakers and its influence on VO2 during LITE. Because aerobic capacity below the anaerobic threshold is more likely to represent activity in daily life and the kinetics of VO2 are significantly related to VO2 at anaerobic threshold and peak exercise, LITE may provide a clinically useful correlate to peak exercise testing.